Caffeic acid phenethyl ester (CAPE) attenuates cerebral vasospasm after experimental subarachnoidal haemorrhage by increasing brain nitric oxide levels - Aladag, MA; Turkoz, Y; Ozcan, C; Sahna, E; Parlakpinar, H; Akpolat, N; Cigremis, Y (Wiley, 2006)
Background: Cerebral vasospasm, a medical complication of aneurysmal subarachnoid hemorrhage (SAH), is associated with high morbidity and mortality rates, even after the aneurysm has been secured surgically or endovascularly. Evidence accumulated during the last decade suggest that scavenging a vasodilator, nitric oxide (NO), by superoxide anions (O-2(-)), and activating a strong vasoconstructor, protein kinase C (PKC), are the two most important mechanisms in the pathogenesis of vasospasm. Our aim in this study was to determine whether caffeic acid phenethyl ester (CAPE), a non-toxic oxygen free radical scavenger, prevents vasospasm in an experimental rat model of SAH. Methods: Twenty eight rats (225-250 g) were divided into four groups equally: group 1, control group group 2, SAH group; group 3, SAH plus placebo group; and group 4, SAH plus CAPE group. We used double haemorrhage method for SAH groups. Starting 6 h after SAH, 10 mu mol/kg CAPE or an equal volume of 0.9% saline were administered by intraperitoneal injection twice daily for 5 days to SAH plus CAPE and SAH plus placebo groups, respectively. CAPE or 0.9% saline injections were continued up to 5th day after SAH. Rats were sacrificed on the 5th day. Brain sections at the level of the pons were examined by light microscopy. Measurements were made for the cross-sectional areas of the lumen and the vessel wall (intimae plus media) of basilar artery by a micrometer. The levels of malondialdehyde (MDA), reduced glutathione (GSH), and nitric oxide (NO) were measured in rat brain tissue. Results: Administration of CAPE significantly attenuated the vasoconstriction of the basilar artery. There were marked narrowing in the lumens of and thickening in the walls of basilar arteries in the SAH, and the SAH plus placebo compared with CAPE group (p < 0.001). We also observed that CAPE administration significantly decreased the tissue level of MDA, while significantly increased the tissue levels of GSH, NO in the SAH plus CAPE group compared to only SAH group, p < 0.05. Conclusions: Our results indicate that CAPE is effective in attenuating delayed cerebral vasoconstriction following experimental SAH. Our findings also suggest that the elevation of lipid peroxidation and reduction of NO bioavailability, resulting from the generation and the interaction of free radicals, have a significant role in the pathogenesis of vasospasm after SAH. (c) 2005 ISDN. Published by Elsevier Ltd. All rights reserved.
Keywords: rat; SAH; vasospasm; CAPE; MDA; GSH; NO